The Blues Brothers. The escape of Joliet Jake - Pisano, Luke; Aykroyd, Stella; Werner, James; Aykroyd, Dan; Belushi, John; Pisano, Judy Belushi (Z2 Comics, 2025)
It's 1997, almost two decades after the events in The Blues Brothers film and Chicago law enforcement is once again in pursuit of the notorious musical criminal, Jake Blues, after a mysterious jailbreak. On the case is Robert, an up and coming detective, whose world is turned upside down... While investigating, Robert receives a little help from Elwood Blues, and an unlikely partnership forms between Robert and Wolfie, an orphan from the Blues Brother's alma-mater, St. Helen's of the Blessed Shroud. Together, they unravel a web of mysteries tied to Blues Brothers adventures with Jake and Elwood that we've never seen before! Get back to the heart of recidivist mischief, soul and bombastic chases. Sink your teeth into a new Blues Brothers adventure.